Novel Method Suggests Global Superiority of Short-Duration Antibiotics for Intra-abdominal Infections. (28th August 2017) - Celestin, Arthur R; Odom, Stephen R; Angelidou, Konstantia; Evans, Scott R; Coimbra, Raul; Guidry, Christopher A; Cuschieri, Joseph; Banton, Kaysie L; O'Neill, Patrick J; Askari, Reza; Namias, Nicholas; Duane, Therèse M; et al.
Abstract: Desirability of outcome ranking and response adjusted for duration of antibiotic risk (DOOR/RADAR) are novel and innovative methods of evaluating data in antibiotic trials. We analyzed data from a noninferiority trial of short-course antimicrobial therapy for intra-abdominal infection (STOP-IT), and results suggest global superiority of short-duration therapy for intra-abdominal infections.